Educational, Social, and Political Activities of Turkish Prisoners of War in Turkestan (1918-1921) - Tojiboev, Jakhongir (The Lingua Spectrum, 2026)
The article analyzes the educational, social, and political activities of Ottoman Turkish prisoners of war who remained in Turkestan amid postwar instability, revolutionary change, and the formation of Soviet rule. It examines the participation of former Ottoman officers in Jadid schools, their influence on youth associations and semi-military groups, their relations with local Muslim communities, and the impact of Bolshevik propaganda among the prisoners. Drawing on archival documents, memoir evidence, and scholarly literature, the study discusses Mustafa Suphi’s activities, the newspaper “Yeni Dünya,” the idea of a Turkish Red Brigade, Ismail Suphi Bey’s meeting with prisoners in Tashkent, and Ankara’s proposals to send teachers and officers to Central Asia. The article argues that Turkish prisoners should be viewed not merely as objects of repatriation policy, but also as active participants in educational reform, social adaptation, ideological mobilization, and transnational political networks in postwar Turkestan. This perspective clarifies their role at the intersection of Jadid reformism, Soviet control, and Anatolian-Asian contacts.